PTU-080 Correlation Of Fdg Pet Scanning With Endoscopic Findings In Patients With Crohn's Disease. (9th June 2014) - Russo, E; Khan, S; Brown, AP; Keat, N; Hallett, W; Janisch, R; Gunn, RN; Rabiner, EA; Matthews, PM; Orchard, TR
Abstract : Introduction: 18 F- Fluoro-deoxy-glucose Positron Emission Tomography (FDG-PET) scanning is gaining popularity in the assessment of several inflammatory disorders including Crohn's Disease (CD). Methods: 11 patients with established CD, underwent 18 F- FDG-PET scanning that was compared with recent endoscopic data, provided treatment had been unchanged between the two tests. Patients were fasted for 6 h and received 185 MBq of iv FDG followed by 800 ml of oral 2.5% mannitol. A low dose CT scan of the abdomen was performed, followed by PET, at 60 min post FDG injection. PET data was acquired over a maximum of 3 bed positions (10 min/ bed position). Analysis involved dividing the gut into 6 segments on CT (terminal ileum, ascending, transverse, descending and sigmoid colon and rectum). Segmental maximum standardised uptake value (SUVMAX ) and SUV intestine-to-liver ratio (SUVITL = SUVMAX /Liver SUVMEAN ) were calculated. A segment is defined as abnormal (PET +ve) when its SUVMAX > Liver SUVMEAN as per previous literature. 1–3 SUVMAX and SUVITL of endoscopically abnormal versus endoscopically normal PET +ve segments were compared using the Mann-Whitney test. Results: 11 patients (52 gut segments) had PET within a median of 1 month of endoscopy. 21/52 segments were active on endoscopy. Of these 20/21 were also PET +ve. However, 17/31 of endoscopically negative segments were alsoPET+ve suggesting a sensitivity of 95% and a specificity of 45% in our cohort. Raising the SUVMAX threshold for defining a PET +ve segment from the existing (>SUVLIVER ) to > 3.5x SUVLIVER reduced sensitivity from 95% to 86%, but improved specificity from 45% to 82% compared to the gold-standard of endoscopy. Conclusion: FDG-PET appears to be up to 95% sensitive in identifying segments with endoscopically active CD. Several 'false positive' segments are also observed conferring a low specificity. A threshold of segmental SUVMAX signal > 3.5 x SUVLIVER greatly improves sensitivity with a minimar reduction in specificity. Segments which demonstrate FDG signal but are negative on endoscopy may reflect disease undetected by endoscopy, or may be false positives. A comparison with histological activity is required to clarify this. References: Louis E, JNM 2007 Meisner, IBD 2007 Das CJ, Eur J Nucl Med Mol Imaging 2007 Disclosure of Interest: None Declared.